The hypocretins and the reward function: what have we learned so far? - Boutrel, Benjamin; Steiner, Nadia; Halfon, Olivier (Frontiers in Behavioral Neuroscience, 2013)
A general consensus acknowledges that drug consumption (including alcohol, tobacco and illicit drugs) constitutes the leading cause of preventable death worldwide. Dramatically, drug abuse is not only a major cause of mortality. The comorbid long-term debilitating effects also significantly deteriorates the quality of life of individuals suffering from addiction disorders. Despite the large body of evidence delineating the cellular and molecular adaptations induced by chronic drug consumption, the brain mechanisms responsible for drug craving and relapse remain insufficiently understood, and even the most recent developments in the field have not brought significant improvement in the management of drug dependence. Though, recent preclinical evidence suggests that disrupting the hypocretin (orexin) system may serve as an anticraving medication therapy. Here, we discuss how the hypocretins, which orchestrate normal wakefulness, metabolic health and the execution of goal-oriented behaviors, may be compromised and contribute to elicit compulsive drug seeking. We propose an overview on the most recent studies demonstrating an important role for the hypocretin neuropeptide system in the regulation of drug reward and the prevention of drug relapse, and we question the relevance of disrupting the hypocretin system to alleviate symptoms of drug addiction.